2022
DOI: 10.21837/pm.v20i22.1140
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Risk Perception and Intention to Improve the Air Quality

Abstract: Numerous environmental issues, particularly those with higher risks, have steadily come to the forefront of the public's concerns in recent years with the increased awareness on environmental quality. For example, air pollution is one of the main causes of death worldwide and contributes to the rise in the risk of chronic diseases. In the Turkish city of Adana, air pollution has long been recognised as a serious environmental and health concern with well-documented negative consequences on human wellbeing. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…For example, Simone et al [42] found significant differences in the perceived levels of air quality among neighbourhoods in two cities. As one of the explanations, socio-institutional approaches [43,44] attribute the inter-group differences in health worries to the notion that societal institutions, infrastructures and information not only shape the opportunities available for individuals to deal with health issues, but also create the societal and individual fears/meanings in a co-evolutionary process. The dominating beliefs about exposure risks, e.g., available information in media coverage, may influence the reports of worry and even symptoms [45].…”
Section: Socio-institutional Context As a Driver Of Risk Perceptionmentioning
confidence: 99%
“…For example, Simone et al [42] found significant differences in the perceived levels of air quality among neighbourhoods in two cities. As one of the explanations, socio-institutional approaches [43,44] attribute the inter-group differences in health worries to the notion that societal institutions, infrastructures and information not only shape the opportunities available for individuals to deal with health issues, but also create the societal and individual fears/meanings in a co-evolutionary process. The dominating beliefs about exposure risks, e.g., available information in media coverage, may influence the reports of worry and even symptoms [45].…”
Section: Socio-institutional Context As a Driver Of Risk Perceptionmentioning
confidence: 99%
“…Reviewing air pollution studies in Adana, Sahrir et al (2022) [16] focused on risk perception and behavior analysis to improve air quality in Adana. Sezer et al (2020) [17] employed a new ANN model to estimate NO x emissions in Adana, contributing to understanding the region's air pollutant emissions and their potential impact on air quality.…”
Section: Introductionmentioning
confidence: 99%